Tragic Optimism as a Buffer Against COVID-19 Suffering and the Psychometric Properties of a Brief Version of the Life Attitudes Scale - Leung, Mega M.; Arslan, Gökmen; Wong, Paul T. P. (Frontiers in Psychology, 2021)
The Life Attitudes Scale (LAS) was designed to measure tragic optimism (TO) - a distinct type of optimism that could generate hopeless hope even in dire situations according to existential positive psychology (PP 2.0). This paper explains why only a faith-based TO as conceptualized by Frankl (1985) and expanded by Wong (2009) could serve as a buffer against suffering at the Nazi death camps as well as the global COVID-19 pandemic. In study one, results showed that the factorial structure of a 15-item Life Attitudes Scale-Brief (LAS-B) which is a short measure of TO replicated the original structure of the 32-item long version (Leung et al., 2003) .The five factors (i.e., affirmation, acceptance, courage, faith, and self-transcendence) provided good data model fit statistics for LAS-B; the measure had adequate-to-strong internal and latent construct reliability estimates. In study two, the buffering effect of TO on the association between suffering experiences during COVID-19 and life satisfaction in adults was examined. The results of the studies were consistent with our hypothesis that TO as measured by LAS-B serves as a buffer against the impact of COVID-19 suffering on life satisfaction.